Real "non-governmental" aid and poverty: comparing privately and publicly financed NGOs in Canada. Issue 3 (3rd July 2019) - Davis, John-Michael
ABSTRACT : Due to their perceived efficiency and poverty orientation, NGOs have increasingly served as Official Development Assistance (ODA) channels, leading scholars to question their autonomy. NGO aid allocation studies have limited analysis to the largest organisations, leaving privately financed NGOs unaccounted for. This study constructs an inventory of Canadian NGOs, segmented by funding source, to determine the influence of ODA. Contrary to entrenched beliefs, Canadian ODA contributes only 9 per cent to Canadian NGO revenue, and privately financed NGOs are less active in the poorest countries than government-subsidised NGOs, suggesting that ODA funding drives NGOs to poorer countries, but has minimal influence on the sector.